Psychometric Properties of the Chinese Version of the Neuroticism Subscale of the NEO-PI - Xi, Chang; Zhong, Mingtian; Lei, Xiaoxia; Liu, Ying; Ling, Yu; Zhu, Xiongzhao; Yao, Shuqiao; Yi, Jinyao (Frontiers in Psychology, 2018)
Neuroticism is an important concept in psychology, self-report measures of neuroticism are important for both research and clinical practice. The neuroticism subscale of the Neuroticism-Extraversion-Openness Personality Inventory (NEO-PI) is a brief measure of neuroticism, and it was widely used in the world. This study was aimed to examine the psychometric properties of the Chinese version of the neuroticism subscale of the NEO-PI. A total of 5,495 undergraduates from three universities and 551 clinical patients with mental disorders from a psychological clinic had completed the Chinese version of the neuroticism subscale of the NEO-PI. Confirmatory factor analysis was performed to examine how well the three hypothetical models fit the data and the measurement equivalence of neuroticism subscale across gender. The internal consistency and test-retest reliability were also evaluated. Both the six-facet model and the bi-factor model (six-facet model with one general factor) achieved satisfactory fit, while the six-facet model had best fit (Undergraduate sample: TLI = 0.919, CFI = 0.933, RMSEA = 0.044, SRMR = 0.033; Clinical sample: TLI = 0.921, CFI = 0.935, RMSEA = 0.047, SRMR = 0.041), and it had measurement equivalence across gender. The neuroticism subscale also showed acceptable internal consistency and good stability. Within the undergraduate sample, there were statistically significant gender differences in neuroticism total scores and scores of six facets, while there were no significant gender differences in the neuroticism scores in the clinical sample. Both in the undergraduate sample and the clinical sample, anxiety facet, depression facet and vulnerability facet of the neuroticism subscale significantly predicted the depression level, while anxiety facet, angry-hostility facet and vulnerability facet significantly predicted the anxiety level. In conclusion, the Chinese version of the neuroticism subscale is a reliable and valid measurement of neuroticism in both undergraduate and clinical population.